Jednokierunkowość odwzorowań metaforycznych a asymetria relacji podobieństwa - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article aims to prove the thesis about the unidirectional nature of metaphor and to indicate a possible explanation for this principle. The main argument in favour of the considered claim is the irreversibility of metaphor. There is only one direction in which a metaphor can function and in reverse it becomes difficult or even impossible for the receiver to interpret. The thesis is validated based on examples from Polish sports press. The article also brings up the relation between metaphor and similarity. As was proven, metaphors are based on a previously perceived (but not necessarily objective) similarity between objects. Thus they inherit the direction of this similarity. (As Amos Tversky claimed in his works, perceiving of similarity between objects is not symmetrical, it is always directed in some way). The asymmetry of similarity relation, as borne out in the article, can be recognised as the main reason of the unidirectional nature of metaphor.